Test to evaluate the technical-tactical development in Beach Volleyball Players in initial stage - Orestes Griego Cairo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2019)
Cuban Beach Volleyball currently does not yet have its Integral Athlete Preparation Program, so the coaches have adapted the evaluation forms of Volleyball to Beach Volleyball without taking into account the differences between both modalities. The objective of the present research is to establish a test to evaluate the technical-tactical development achieved by beach volleyball players, thus responding to one of the current technological demands of the Cuban Volleyball Federation. Theoretical research methods (synthesis, inductive-deductive and documentary analysis) and empirical (interviews) were used. Methodological workshops were carried out with beach volleyball trainers, which allowed the design of the test, its conformation and, later, its evaluation through specialist criteria. A test that takes into account the characteristics that identify the Beach Volleyball game is conceived. The specialists consulted consider that the test developed is adequate, on the basis of its relevance, the parameters of formal quality and practical usefulness that it possesses. The results obtained from the design and structuring allowed to conclude that the essence of this result permits to evaluate the technical-tactical development reached by the players of this sport in the initiation, from the indissoluble link between technique and tactics.